From Vulnerability to Transformation: The Self in Haddon’s The Curious Incident of the Dog in the Night-Time - Neupane, Pimala (SCHOLARS: Journal of Arts & Humanities, 2022)
This paper examines Mark Haddon’s The Curious Incident of the Dog in the Night-Time applying the theory of abjection, which portrays the self-transformation of the protagonist, Christopher Boone, from the Swindon city in the UK. He performs his extraordinary self from the subordinated condition in the novel. At fifteen, Christopher who is suffering from Asperger’s Syndrome remains in a state of helplessness and vulnerable when neglected by all. However, he explores relevant ideas and effective strategies after analyzing himself and his surroundings minutely. An abject adolescent, he fails to understand others properly nor do other people clearly understand him. In the paper, I examine the protagonist’s transformation into a responsible member of the family, an ethical person in the society and a savior of all the creatures. In other words, his personal self is changed into companionship from isolation, logic from disorder and life even for pet animals from a deadly situation. He not only finds out the murderer of the dog, but also he presents the reason behind actions such as the unhealthy relationship of human beings in the family and society, and their unfair treatment to other creatures. This study is descriptive-analytical and secondary data are collected from different sources in order to address the issues raised in the study. The concept of abjection as developed by Karen Coats has been adopted for analysis of the text that is the major characteristic of young adult literature. The novel selected for this study is a young adult literary text and the novelist is an abject young adult.